Răspuns :
{2×[14+(5+X):6]-5}:9+7=10 /-7
{2×[14+(5+X):6]-5}:9=3 /×9
2×[14+(5+X):6]-5=27 /+5
2×[14+(5+X):6]=32 /:2
14+(5×X):6=16 /+14
(5+X):6= 30 /:6
5+X=5 /+5
X=10
{2×[14+(5+X)÷6]-5}÷9+7=10 |-7
{2×[14+(5+X)÷6]-5}÷9=3 |×9
2×[14+(5+X)÷6]-5=27 |+5
2×14+(5+X)÷6=32
28+(5+X)÷6=32 |-28
(5+X)÷6=4 |×6
5+X=24 |-5
X=19
verificare
{2×[14+(5+19)÷6]-5}÷9+7=10
{2×[(14+24÷6)-5]}÷9+7=10
[(2×(14+4)-5]÷9+7=10
[(2×16)-5]÷9+7=10
(32-5)÷9+7=10
27÷9+7=10
3+7=10
{2×[14+(5+X)÷6]-5}÷9=3 |×9
2×[14+(5+X)÷6]-5=27 |+5
2×14+(5+X)÷6=32
28+(5+X)÷6=32 |-28
(5+X)÷6=4 |×6
5+X=24 |-5
X=19
verificare
{2×[14+(5+19)÷6]-5}÷9+7=10
{2×[(14+24÷6)-5]}÷9+7=10
[(2×(14+4)-5]÷9+7=10
[(2×16)-5]÷9+7=10
(32-5)÷9+7=10
27÷9+7=10
3+7=10